Gestational gigantomastia—a rare entity complicated by life-threatening haemorrhage. Issue 4 (14th April 2021) - Neblett, Carlos; Venugopal, Rajeev; Johnson, Miguel; Mitchell, Derek; Kunc, Vojtech
Abstract: Gestational gigantomastia is a psychologically and physically debilitating disease of unknown aetiology. Underlying diseases that present as gigantomastia should be excluded by a thorough workup. Most cases respond to the preferred approach: conservative management, as foetal viability and well-being is of significant importance. However, in those cases where the maternal mortality is at risk, the surgical approach is preferred. Life-threatening haemorrhage may occur and early recognition and treatment is paramount to outcome. A case of gestational gigantomastia complicated by life-threatening haemorrhage is presented and discussed.